Kajian Morfologis dan Kelimpahan Ikan Sili (Famili : Mastacembelidae) di Sungai Seruai Desa Namu Suro Kabupaten Deli Serdang Provinsi Sumatera Utara “Morphological Studies and Abundance of Sili Fish (Family: Mastacembelidae) in Seruai River Namu Suro Vill - Ali Yunus; Miswar Budi Mulya; Irwanmay Irwanmay (AQUACOASTMARINE, 2017)
Sili Fish (Family: Mastacembelidae) can be characterized by an elongated proboscis down the snout. Family Mastacembelidae are divided into three genera namely Mastacembelus (61 species), Macrognathus (24 species), and Sinobdella (1 species). The Research on Sili Fish is still limited, even for the North Sumatra region has never been done before. Seruai River is one of the rivers in North Sumatra that obtained Sili Fish populations. This raserch aimed to determine the character of Morphological and Abundance of Sili Fish (Family: Mastacembelidae) in Seruai River. This research was conducted in August 2016. The result showed that Sungai Seruai only have two species of Sili Fish, They are Mastacembelus unicolor (yellow hue on the parallel roundly body, caudal fin separate from dorsal and anal fins) and Mastacembelus notophthalmus (there are black vertical lines on the muzzle area nearby the eye , caudal fin merges with the dorsal and anal fins). The abundance of Sili fish with the use of 0.15 ind/m² and 0.07 ind/m² nets are in station 1 and 3. The abundance value by using 2.13 ind/m² traps is only found in the station 2. The attendance of Sili Fish is very rarely to be found.Keywords : Abundance, Mastacembelus unicolor, Mastacembelus notophthalmus, Seruai River.